The dynamics of 3D diocotron wave during the “hot“ electron flow propagation in the drift space - Tarasov, M.I.; Tarasov, I.K.; Sitnikov, D.A. (Вопросы атомной науки и техники, 2012)
The longitudinal dynamic effect on the diocotron wave evolution was clarified. The main features of the plasma particles trapping and confining during the ‘hot’ electron beam propagation through the space of drift were studied.